Neurocognitive Dysfunction According to Hypoperfusion Territory in Patients With Moyamoya Disease - Kang, Chang Gu; Chun, Min Ho; Kang, Jung-A; Do, Kyung Hee; Choi, Su Jin (Annals of rehabilitation medicine, 2017)
To demonstrate the prevalence of cerebral hypoperfusion without focal cerebral lesions in patients with Moyamoya disease (MMD), and the relationship between areas of hypoperfusion and cognitive impairment. Twenty-six MMD patients were included. Patients were categorized according to the presence/absence of hypoperfusion in the frontal, parietal, temporal, and occipital lobes on brain single-photon-emission computed tomography (SPECT) after acetazolamide challenge. Computerized neuropsychological test (CNT) results were compared between groups. Only 3 patients showed normal cerebral perfusion. Baseline characteristics were similar between groups. Patients with frontal lobe hypoperfusion showed lower scores in visual continuous performance test (CPT), auditory CPT, forward digit span test, backward digit span test, verbal learning test, and trail-making test. Patients with parietal lobe hypoperfusion showed lower backward digit span test, visual learning test, and trail-making test scores. Related to temporal and occipital lobes, there were no significant differences in CNT results between the hypoperfusion and normal groups. MMD patients without focal cerebral lesion frequently exhibit cerebral hypoperfusion. MMD patients with frontal and parietal hypoperfusion had abnormal CNT profiles, similar to those with frontal and parietal lesions. It is suggested that the hypoperfusion territory on brain SPECT without focal lesion may affect the characteristics of neurocognitive dysfunction in MMD patients.